Pandharpur Wari: Pilgrim Sojourn in the City of Pune - Suchetana Banerjee; Gayatri Mendanha; Ananya Dutta (Dastavezi)
The Pandharpur wari is an iconic annual pilgrimage in Maharashtra that starts from the towns of Alandi and Dehu. It has a rich tradition dating back to the thirteenth century. The wari (Marathi term for pilgrimage, also associated with the specific pilgrimage to the temple town of Pandharpur) involves hundreds of thousands of devotees known as varkaris walking for 21 days through villages and cities, traveling around 250 kilometers by foot to meet their beloved deity Vitthal at his temple in Pandharpur. The pilgrimage, passing through the city of Pune, is a significant event, because it transforms the city’s atmosphere into one of devout reverence and collective celebration for three days. Varkaris carry with them padukas, impressions of the feet of saintly poets of Maharashtra, to meet Vitthal. The poet–god relationship, central to the wari, underscores a devotional ethos that is inclusive and accessible to the common person, reinforcing the ideals of mutual respect and coexistence. In an era marked by political fragmentation, the Pandharpur wari stands as an example of hope, enacting how cultural and spiritual practices can bridge divides and cultivate a sense of collective identity and solidarity. Thus, the wari is more than a pilgrimage; it is a living tradition that fosters unity and love and is a testament to enduring faith and communal harmony. This audiovisual essay offers an immersive experience of the wari in Pune.